Direct‐acting antiviral regimens are safe and effective in the treatment of hepatitis C in simultaneous liver–kidney transplant recipients. Issue 3 (1st February 2018) - Nookala, Anupama U.; Crismale, James; Schiano, Thomas; Te, Helen; Ahn, Joseph; Robertazzi, Suzanne; Rodigas, Colleen; Satoskar, Rohit; KC, Mandip; Hassan, Mohamed; Smith, Coleman
Abstract: Hepatitis C (HCV) remains the single most common etiology of end‐stage liver disease leading to simultaneous liver/kidney transplant (SLKT) and has worse post‐transplant survival compared to non‐HCV patients. We aim to assess the effectiveness and tolerance of the all‐oral direct‐acting antiviral (DAA) agents with or without ribavirin (RBV) in the treatment of HCV recurrence post‐SLKT. Thirty‐four patients were studied retrospectively, composed predominantly of treatment‐naïve (73.5%) non‐Caucasian (61.8%) males (82.4%) infected with genotype 1a (64.7%). 94.1% reached a sustained virologic response (SVR) after 24 weeks (32/34 patients), without difference between 12 and 24 weeks of therapy. 64.7% had no clinical side effects. Three deaths occurred, all unrelated to treatment. One patient had liver rejection; tacrolimus was increased and prednisone was initiated while HCV treatment was continued and the patient ultimately achieved SVR. No liver graft losses. No kidney rejection or losses. We demonstrated that DAA combinations with or without RBV result in a remarkable SVR rate and tolerated in the majority of the studied SLKT patients. It is safe to wait to treat until post–kidney transplant and therefore increase the donor pool for these patients. Our cohort is ethnically diverse, making our results generalizable.